Do accelerator programs enhance the founders’ entrepreneurial self-efficacy? - Muqbel, Tarek Patrick (2018)
This thesis attempts to contribute to the knowledge of entrepreneurship education, namely how targeted education and training may foster entrepreneurial intentions, activity and performance. More specifically, the objective of this work is to research the effect that the participation in an accelerator program has on the participants’ “entrepreneurial self-efficacy” (ESE) – the perceived competence to perform the various tasks associated with entrepreneurship. ESE is considered as a key antecedent of entrepreneurial intentions and thus successful entrepreneurial activity. Given the malleability of the concept, various stakeholders show interest in enhancing ESE, mainly through specific education and training in entrepreneurship education programs (EEP’s). Our sample is based on 34 entrepreneurs from 15 different nationalities who just recently participated in a top-accelerator program worldwide. The participants were asked to assess their self-perceived confidence to perform certain tasks associated with entrepreneurship before and after the program. Using a paired- and independent as well as the Wilcoxont signedrank test, the participants ESE scores were significantly higher after the program than before the program providing evidence that the educational methods used in accelerator programs are indeed effective in enhancing ESE. Entrepreneurship promoting entities (e.g. EEP’s, Business Schools) can draw valuable insights from the educational methods applied in accelerator programs and should consider adapting their teaching styles and curricula respectively.